Meningkatkan Hasil Belajar Siswa Pada Muatan IPA Tema Selalu Berhemat Energi Melalui Model Pembelajaran Problem Based Learning di Kelas IV SD Negeri 219/X Pandan Lagan - Suningram Suningram (Departement of Mathematics Education, 2022)
This study aims to disclose information and discuss about Improving Student Learning Outcomes on Science Content with the Theme of Always Saving Energy Through Problem Based Learning Models in Class IV SD Negeri 219/X Pandan Lagan. This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 209/X Pandan Lagan. The time of this research was carried out in the odd semester of the academic year 2021 - 2022, which began in August 2021. The subjects in this study were grade IV students, totaling 20 people. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using observation sheets, field notes, learning outcomes test sheets, and documents. Data were analyzed using the percentage formula. The results of this study indicate that through the Problem Based Learning Learning Model on the Theme of Always Saving Energy, it can improve student learning outcomes in grade IV SD Negeri 209/X Pandan Lagan which is marked by an increase from pre-cycle (30%), cycle I (45%), cycle II (80%).